Functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent and preparation method thereof
By using double-end vinyl imidazole bromide ionic liquid as crosslinking agent, functional ionic liquids enhance the granule blocking agent of polyacrylamide gels, solving the temperature resistance of polyacrylamide gels in high temperature and high pressure environments and The problem of insufficient stability has achieved efficient sealing effect and environmental protection performance, and is suitable for oil and gas mining.
Patent Information
- Application Number
- CN202411250230.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The existing polyacrylamide gels are insufficient in high temperature and high pressure environments, resulting in poor sealing effect during oil field mining, and traditional crosslinking agents have toxicity and environmental pollution problems.
Using double-end vinyl imidazole bromide ionic liquid as crosslinking agent, functional ionic liquids are prepared through free radical polymerization, microfluidic technology and titration gel method to enhance the thermal stability and Compressive strength and enhance its environmental compatibility through coating treatment.
It significantly improves the thermal stability and compressive strength of gel particles, extends service life, reduces environmental pollution, is suitable for oil and gas mining in high-temperature and high-pressure environments, and has good economic benefits and market prospects.
Smart Images

Figure CN119119358A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of gel particles, and in particular relates to a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent and a preparation method thereof. Background Art
[0002] The presence of amide groups in the acrylamide molecular chain shows extremely strong hydrophilicity. After the introduction of chemically modified ionizable functional groups. Since the added ionizable groups carry charges, electrostatic repulsion occurs, and the molecular chains are in a relaxed state and dispersed separately, so that the volume share in the aqueous solution is large and has a thickening effect. This is also the reason why polyacrylamide is the most widely used. When polyacrylamide is placed in water, the molecular chains in the polyacrylamide will entangle with each other, and the molecular chains will cross-link and overlap into a network structure, which will increase the viscosity of the solution to achieve a thickening effect. This thickening effect will increase as the concentration of polyacrylamide in the system increases. Based on the easy modification of polyacrylamide, functional polyacrylamide gel can be prepared. The introduction of monomers with functional characteristics into the gel network can not only improve the conductivity of the gel, but also enhance its mechanical properties and biocompatibility, giving the gel new functional responsiveness while breaking through the limitations of traditional gels, which poses a challenge to the selection and preparation technology of water plugging materials at this stage. Therefore, it is crucial to develop gel polymer materials suitable for the current oil field exploitation environment to significantly increase the oil recovery rate. Among the various profile control and water plugging agents studied at home and abroad, polyacrylamide gel plugging agents are the most widely used. This type of gel plugging agent can control conditions and facilitate injection; it not only has strong selectivity for high water-containing strata, but also has significant effects on plugging reservoirs such as high permeability sandstone reservoirs, fractured and large-pore reservoirs. Therefore, research on polyacrylamide gel composite materials in the field of oil extraction is particularly important.
[0003] Through the above analysis, the problems and defects of the prior art are as follows:
[0004] At present, the most commonly used acrylamide gels have limited use due to their average temperature resistance, gel strength and stability. During use, as the temperature rises, the degradation rate decreases faster, the gel strength decreases faster, and even no blocking effect occurs. Existing gel polymer materials cannot solve these problems well, and it is necessary to reasonably utilize the characteristics of gel polymer materials to prepare gels that meet the needs of certain specific areas.
[0005] Among the various profile control and water plugging agents studied at home and abroad, polyacrylamide gel plugging agents are the most widely used. This type of gel plugging agent can control conditions and is convenient for injection. It not only has strong selectivity for high water-bearing strata, but also has significant effects on plugging reservoirs such as high permeability sandstone reservoirs, fractured reservoirs and large pore reservoirs. Therefore, the research on polyacrylamide gel composite materials in the field of oil production is particularly important. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a functional ionic liquid reinforced polyacrylamide-based gel particle plugging agent and a preparation method thereof.
[0007] The present invention is implemented in this way: a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent has the following structure:
[0008]
[0009] Furthermore, the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent uses a copolymer of acrylic acid AA and acrylamide AM as a basic gel material.
[0010] Another object of the present invention is to provide a method for preparing a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent, comprising:
[0011] (1) Preparation of prepolymer solution;
[0012] (2) Preparation of P(AA-AM-ILs) gel particle plugging agent.
[0013] (3) Coated gel particle plugging agent.
[0014] Further, the preparation of the prepolymer solution;
[0015] Add acrylic acid and 6 mL of distilled water to a 50 mL beaker. Slowly add sodium hydroxide under magnetic stirring and ice-water bath conditions to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, weigh a certain amount of acrylamide solid and add it;
[0016] Then weigh a certain amount of β-hydroxyethyl methacrylate and slowly add it; during the stirring process, add a certain amount of ionic liquid crosslinking agent to the above-prepared solution, and the addition amount is as shown in the table; finally, add potassium persulfate with a total weight of 0.8% of acrylic acid and acrylamide, and ensure that no solid remains on the wall of the cup during the addition process; after all the reagents required for the experiment are added, continue to stir until the mixture is evenly mixed to perform a crosslinking reaction to obtain a prepolymer solution.
[0017] Furthermore, the mass ratio of acrylamide to acrylic acid is 6:4.
[0018] Further, the preparation of the P(AA-AM-ILs) gel particle plugging agent:
[0019] Use a syringe to absorb the prepared prepolymer liquid and drop it into 80℃ constant temperature silicone oil. Be careful not to have bubbles when the syringe absorbs the precursor liquid. React for 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with tetrahydrofuran. Wash it several times, ventilate and dry it at room temperature for 3 hours, put it in a 70℃ oven, and dry it to constant weight to obtain spherical polyacrylamide gel particles, which are bagged for later use.
[0020] Furthermore, the coated gel particle plugging agent:
[0021] The spherical gel particle plugging agent is coated with octadecyltrimethoxysilane. The specific operation steps are as follows: add a certain amount of solvent toluene and octadecyltrimethoxysilane (OTS) into a three-necked flask, mechanically stir at room temperature for 48 hours, and after the reaction is completed, dry the sample at room temperature for 12 hours to obtain the target product, which is then bagged for later use.
[0022] Another object of the present invention is to provide a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent preparation system comprising:
[0023] The prepolymer liquid preparation module is used to add acrylic acid and 6 mL of distilled water into a 50 mL beaker, and slowly add sodium hydroxide under magnetic stirring and ice water bath conditions to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, a certain amount of acrylamide solid is weighed and added; then a certain amount of β-hydroxyethyl methacrylate is weighed and slowly added; during the stirring process, a certain amount of ionic liquid crosslinking agent is added to the above-prepared solution, and the addition amount is as shown in the table, and finally potassium persulfate is added at 0.8% of the total mass of acrylic acid and acrylamide, and the addition process ensures that no solid remains on the wall of the cup; after all the reagents required for the experiment are added, stirring is continued until the mixture is evenly mixed to perform a crosslinking reaction to obtain a prepolymer liquid;
[0024] Preparation module of gel particle plugging agent: use a syringe to absorb the prepared prepolymer solution and drop it into 80℃ constant temperature silicone oil. Be careful not to have bubbles when the syringe absorbs the precursor solution. React for 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with tetrahydrofuran for several times. Dry it for 3 hours under ventilation at room temperature, put it in a 70℃ oven, dry it to constant weight, and obtain spherical polyacrylamide gel particles, which are bagged for later use.
[0025] The coated gel particle plugging agent module is used to coat the spherical gel particle plugging agent with octadecyltrimethoxysilane. The specific operation steps are as follows: add a certain amount of solvent toluene and octadecyltrimethoxysilane (OTS) into a three-necked flask, mechanically stir at room temperature for 48 hours, and after the reaction is completed, dry the sample at room temperature for 12 hours to obtain the target product, and bag it for later use.
[0026] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0027] First, in view of the technical problems existing in the above-mentioned prior art, some creative technical effects are brought about after solving the problems. The specific description is as follows:
[0028] (1) The present invention designs a novel polymer gel particle plugging agent based on an ionic liquid crosslinker that can be used for oil well fracturing transformation.
[0029] (2) The present invention adopts free radical polymerization, microfluidic technology and titration gel method to prepare polymer gel particle plugging agent, and the preparation process is simple.
[0030] (3) The present invention uses ionic liquid as a cross-linking agent to prepare a gel particle plugging agent. The ionic liquid has good thermal stability and stable chemical properties. Compared with the gel particle plugging agent prepared with an ordinary cross-linking agent, the gel particle plugging agent prepared with ionic liquid as a cross-linking agent has better stability, high temperature resistance and compressive strength.
[0031] (4) The experimental results show that when the content of the ionic liquid crosslinker reaches 1.5%, the compressive strength of the polymer gel particles reaches the maximum value. This shows that within a certain range, an appropriate amount of ionic liquid crosslinker can effectively enhance the mechanical properties of the gel particles. The addition of the ionic liquid crosslinker significantly improves the strength of the gel particles, and the ionic liquid itself has high mechanical properties, which increases its compressive strength.
[0032] (5) Experimental results show that ionic liquids as cross-linking agents can improve the thermal stability of polymer gel particles and increase their performance under high temperature conditions.
[0033] Second, as auxiliary evidence of the inventiveness of the claims of the present invention, it is also reflected in the following important aspects:
[0034] (1) The expected benefits and commercial value of the technical solution of the present invention after transformation are:
[0035] Market demand: This technology can effectively solve the leakage problem in oil and gas extraction, improve the recovery rate, meet industry needs, and has broad market prospects.
[0036] Cost saving: By increasing oil and gas recovery and reducing leakage, production costs are reduced and economic benefits are improved.
[0037] Production efficiency: Functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent can significantly improve production efficiency due to its excellent performance and efficient plugging effect.
[0038] Technological leadership: This technical solution utilizes double-terminated vinyl imidazolium bromide ionic liquid as a cross-linking agent, which is unique and innovative and provides a technological advantage.
[0039] Market share: With the unique performance and remarkable effects of this technology, it can quickly occupy the market and increase the company's market share.
[0040] Environmental protection: Double-terminated vinyl imidazolium bromide ionic liquid as a cross-linking agent has good environmental compatibility, can reduce environmental pollution during the mining process, and meets environmental protection requirements.
[0041] Sustainable development: The application of technology helps to achieve efficient use of resources and sustainable development, which is in line with modern society's pursuit of environmental protection and sustainable development.
[0042] Oil and Gas: This technology has broad application prospects in oil and gas production, which can improve recovery and reduce leakage.
[0043] Geothermal energy: The technology can also be applied to geothermal energy development, helping to improve the efficiency of geothermal wells.
[0044] In summary, the technical solution of synthesizing functional ionic liquid-enhanced polyacrylamide-based gel particle plugging agent and its preparation method using double-terminal vinyl imidazolium bromide ionic liquid as cross-linking agent can not only bring significant economic benefits, but also enhance the market competitiveness and brand value of enterprises, and has broad commercial value and social benefits.
[0045] (2) The technical solution of the present invention fills the technical gap in the industry at home and abroad:
[0046] Material selection: Double-terminal vinyl imidazolium bromide ionic liquid is used as a crosslinker and combined with polyacrylamide-based materials. Double-terminal vinyl imidazolium bromide ionic liquid has good chemical stability and adjustable physical and chemical properties, which helps to form a stable crosslinking network.
[0047] Synthesis process: Under specific conditions, a double-terminated vinyl imidazolium bromide ionic liquid is mixed with acrylamide monomer to generate a cross-linked polyacrylamide gel through polymerization. This process can control the mechanical properties and structural characteristics of the gel by adjusting the reaction conditions (such as temperature, time, initiator concentration, etc.).
[0048] High strength properties: The synthesized polyacrylamide-based gel particles have high mechanical strength and stability, and can maintain structural integrity under harsh environments such as high pressure and high temperature. Its excellent mechanical properties make it suitable for water plugging and production enhancement measures in oil and gas production.
[0049] Application areas: This high-strength gel particle plugging agent is mainly used for water plugging and production increase in oil and gas fields. It has good corrosion resistance and aging resistance, can effectively improve oil and gas production efficiency, and reduce environmental pollution and resource waste.
[0050] In general, this technical solution successfully prepared functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent by innovatively using double-terminal vinyl imidazolium bromide ionic liquid as a cross-linking agent, filling the technical gap in this field at home and abroad, and providing a new type of efficient and environmentally friendly material for oil and gas field development.
[0051] (3) The technical solution of the present invention solves the technical problems that people have been eager to solve but have never been able to solve successfully:
[0052] Green and environmentally friendly cross-linking agents: Traditional cross-linking agents have toxicity or environmental pollution problems, while ionic liquids as cross-linking agents not only have good biocompatibility, but also can reduce the burden on the environment.
[0053] Gel particle strength and stability: Using ionic liquids as cross-linking agents can improve the mechanical strength and thermal stability of polyacrylamide-based gel particles, thereby increasing the service life and effectiveness of the plugging agent.
[0054] Controlling the size and morphology of gel particles: The use of ionic liquids can better control the size and morphology of gel particles, making them better adapted to different water plugging requirements in practical applications.
[0055] Highly efficient water plugging performance: By optimizing the type and dosage of ionic liquids, the water plugging performance of gel particle plugging agents can be significantly improved, thereby improving the efficiency of oil field production.
[0056] This technical solution has obvious advantages in environmental protection, material performance, application effect, etc. It solves some problems faced by traditional plugging agents during use and has important application value and prospects.
[0057] (4) The technical solution of the present invention overcomes technical prejudice:
[0058] 1. Prejudice against the application of ionic liquids: Traditionally, although ionic liquids are considered to have many excellent properties, many people are skeptical about their application in actual industry due to their high cost, complex synthesis and lack of in-depth research on their application. Through this invention, the effectiveness of ionic liquids as cross-linking agents has been verified, breaking the prejudice against their application limitations.
[0059] 2. Prejudice on the performance of gel particles: In the past, people often believed that high-performance gel particles were difficult to synthesize and expensive. This technical solution successfully synthesized high-strength and high-stability polyacrylamide-based gel particles by using ionic liquids, proving that the synthesis of high-performance materials can be achieved under economically feasible conditions.
[0060] 3. Prejudice that environmental protection and performance cannot be achieved at the same time: Many people believe that high-performance materials are often accompanied by high pollution and high energy consumption. The application of ionic liquids as green cross-linking agents has proved that environmental protection and low energy consumption can be achieved while improving material performance, changing people's view that high-performance materials and environmental protection cannot be achieved at the same time.
[0061] 4. Bias on the acceptance of new materials: People tend to be conservative about the application of new materials, especially in traditional industrial fields. The successful application of this technical solution demonstrates the potential and advantages of new materials in actual industry, and helps promote the acceptance and popularization of new material technology.
[0062] Third, the technical solution of the present invention aims at the deficiencies in the prior art and provides a functional ionic liquid reinforced polyacrylamide-based gel particle plugging agent, which solves the deficiencies of traditional plugging agents in terms of strength and stability. In the prior art, polyacrylamide-based plugging agents are prone to strength loss and particle decomposition under high temperature and high pressure environments, resulting in unstable plugging effects, which in turn affects the safety and efficiency of engineering operations.
[0063] By introducing a copolymer of acrylic acid (AA) and acrylamide (AM) as a basic material, the technical solution of the present invention significantly improves the strength and durability of the gel particles, and can maintain structural integrity and stable performance under high temperature and high pressure environments. In addition, by rationally selecting initiators and cross-linking agents and optimizing polymerization conditions, the prepared gel particles have better plugging effects and the ability to resist environmental stress. This technological advancement has important application value in the fields of oil and gas extraction, geological engineering, etc., and can greatly improve the safety and efficiency of operations, extend the service life of equipment, and reduce maintenance costs.
[0064] Therefore, the present invention has achieved significant technical progress while solving the problems of the prior art, and has provided a more reliable and efficient solution for engineering applications in related fields.
[0065] Fourth, the technical solution of the present invention provides a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent and a preparation method thereof to address the problems of insufficient strength, poor stability and easy failure of plugging agents in high temperature and high pressure environments in the prior art. In the application process, polyacrylamide-based plugging agents in the prior art are often limited by the physical and chemical properties of the materials, resulting in the failure of the plugging agents in extreme environments and the inability to effectively achieve the purpose of plugging.
[0066] The present invention significantly improves the strength and environmental resistance of the plugging agent by improving the preparation steps of the prepolymer solution, especially introducing an ionic liquid as a crosslinking agent, and optimizing the ratio of acrylic acid to acrylamide. During the preparation process, the addition speed and neutralization degree of sodium hydroxide are accurately controlled under ice-water bath conditions to ensure the complete reaction of acrylic acid, thereby improving the stability of the prepolymer solution. In addition, β-hydroxyethyl methacrylate is used as a functional monomer and combined with an ionic liquid crosslinking agent to further enhance the structural strength of the gel particles, so that it can maintain a good plugging effect under high temperature and high pressure environments.
[0067] This technical solution not only solves the key problems in the prior art, but also makes significant progress in material selection and preparation process. The improved functional ionic liquid reinforced polyacrylamide-based gel particle plugging agent has higher strength, better temperature resistance and pressure resistance, and can be widely used in oil and gas production, geological engineering and other fields, providing a more reliable solution for plugging needs in complex operating environments. These technological advances make the present invention have significant application value and competitive advantages in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 The present invention provides a flow chart of a method for preparing a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent.
[0069] Figure 2 This is a structural block diagram of a system for preparing a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent provided by an embodiment of the present invention.
[0070] Figure 3 This is a macroscopic morphology of the polymer gel particles prepared according to an embodiment of the present invention.
[0071] Figure 4 It is a scanning electron microscope image of the cross section of the polymer gel particles prepared according to the embodiment of the present invention.
[0072] Figure 5 It is an analysis diagram of the FTIR spectrum of P(AA-AM-ILs) provided in an embodiment of the present invention.
[0073] Figure 6 This is a thermal stability analysis chart of the synthesized polymer gel provided in an embodiment of the present invention at 30°C-800°C.
[0074] Figure 7 It is a curve diagram showing the relationship between the amount of ionic liquid crosslinking agent used and the strength of polymer gel particles at different temperatures provided by an embodiment of the present invention.
[0075] Figure 8It is a curve diagram of water absorption rate and temperature of the polymer gel particles provided in the embodiment of the present invention.
[0076] Fig. 9 3 is a contact angle diagram of the coated polymer gel particles provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0077] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0078] The structure of a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent provided in an embodiment of the present invention is as follows:
[0079]
[0080] The functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent provided in the embodiment of the present invention adopts a copolymer of acrylic acid AA and acrylamide AM as a basic gel material.
[0081] The following are two specific examples, describing different formulations and preparation methods of functional ionic liquid enhanced polyacrylamide-based gel particle plugging agents:
[0082] Example 1
[0083] In this embodiment, the preparation of the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent includes the following steps:
[0084] 1. Selection of base materials: Acrylic acid (AA) and acrylamide (AM) are selected as copolymers and mixed in a mass ratio of 3:7.
[0085] 2. Initiation of polymerization reaction: Add initiator ammonium persulfate (APS) and cross-linking agent N,N'-methylenebisacrylamide (MBA) to the mixed solution, and carry out free radical polymerization reaction at 60°C to form high-strength polyacrylamide-based gel particles.
[0086] 3. Gel granulation: The obtained gel material is prepared into particles with a particle size of 0.1-0.5 mm by shearing or grinding, and then the particles are dried to obtain the final high-strength plugging agent.
[0087] Example 2
[0088] In this embodiment, the preparation of the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent includes the following steps:
[0089] 1. Selection of base materials: Acrylic acid (AA) and acrylamide (AM) are selected as copolymers and mixed in a mass ratio of 1:1.
[0090] 2. Initiation of polymerization reaction: Potassium persulfate (KPS) is added to the mixed solution as an initiator, and a small amount of N,N'-methylenebisacrylamide (MBA) is added as a cross-linking agent, and a polymerization reaction is carried out at 70°C to form a gel.
[0091] 3. Particle preparation: The prepared gel is mechanically sheared into particles with a particle size of 0.5-1.0 mm. The particles are then washed with ethanol and dried at low temperature to finally obtain a high-strength gel particle plugging agent with excellent plugging performance.
[0092] These two examples demonstrate the method of preparing functional ionic liquid-reinforced polyacrylamide-based gel particle plugging agents with different specifications and properties by changing the ratio of acrylic acid to acrylamide and the polymerization conditions.
[0093] like Figure 1 As shown, a method for preparing a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent provided in an embodiment of the present invention comprises:
[0094] S101, preparation of prepolymer solution;
[0095] S102, preparation of P(AA-AM-ILs) gel particle plugging agent;
[0096] S103, coated gel particle plugging agent.
[0097] Preparation of prepolymer solution provided by an embodiment of the present invention;
[0098] Add acrylic acid and 6 mL of distilled water to a 50 mL beaker. Slowly add sodium hydroxide under magnetic stirring and ice-water bath conditions to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, weigh a certain amount of acrylamide solid and add it;
[0099] Then weigh a certain amount of β-hydroxyethyl methacrylate and slowly add it; during the stirring process, add a certain amount of ionic liquid crosslinking agent to the above-prepared solution, and the addition amount is as shown in the table; finally, add potassium persulfate with a total weight of 0.8% of acrylic acid and acrylamide, and ensure that no solid remains on the wall of the cup during the addition process; after all the reagents required for the experiment are added, continue to stir until the mixture is evenly mixed to perform a crosslinking reaction to obtain a prepolymer solution.
[0100] Table 1 Addition ratio of ionic liquid crosslinking agent
[0101]
[0102] The mass ratio of acrylamide to acrylic acid provided in the embodiment of the present invention is 6:4.
[0103] Preparation of P(AA-AM-ILs) gel particle plugging agent provided in the embodiment of the present invention:
[0104] Use a syringe to absorb the prepared prepolymer liquid and drop it into 80℃ constant temperature silicone oil. Be careful not to have bubbles when the syringe absorbs the precursor liquid. React for 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with tetrahydrofuran. Wash it several times, ventilate and dry it at room temperature for 3 hours, put it in a 70℃ oven, and dry it to constant weight to obtain spherical polyacrylamide gel particles, which are bagged for later use.
[0105] The coated gel particle plugging agent provided in the embodiment of the present invention:
[0106] The spherical gel particle plugging agent is coated with octadecyltrimethoxysilane. The specific operation steps are as follows: add a certain amount of solvent toluene and octadecyltrimethoxysilane (OTS) into a three-necked flask, mechanically stir at room temperature for 48 hours, and after the reaction is completed, dry the sample at room temperature for 12 hours to obtain the target product, which is then bagged for later use.
[0107] like Figure 2 As shown, a functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent preparation system provided in an embodiment of the present invention comprises:
[0108] The prepolymer liquid preparation module is used to add acrylic acid and 6 mL of distilled water into a 50 mL beaker, and slowly add sodium hydroxide under magnetic stirring and ice water bath conditions to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, a certain amount of acrylamide solid is weighed and added; then a certain amount of β-hydroxyethyl methacrylate is weighed and slowly added; during the stirring process, a certain amount of ionic liquid crosslinking agent is added to the above-prepared solution, and the addition amount is as shown in the table, and finally potassium persulfate is added at 0.8% of the total mass of acrylic acid and acrylamide, and the addition process ensures that no solid remains on the wall of the cup; after all the reagents required for the experiment are added, stirring is continued until the mixture is evenly mixed to perform a crosslinking reaction to obtain a prepolymer liquid;
[0109] The gel particle plugging agent preparation module is used to draw the prepared prepolymer liquid with a syringe and drop it into the 80°C constant temperature silicone oil. When the syringe draws the precursor liquid, be careful not to have bubbles. The reaction is 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with tetrahydrofuran for several times. Dry it for 3 hours under ventilation at room temperature, put it in a 70°C oven, dry it to constant weight, and obtain spherical polyacrylamide gel particles, which are bagged for later use;
[0110] The coated gel particle plugging agent module is used to coat the spherical gel particle plugging agent with octadecyltrimethoxysilane. The specific operation steps are as follows: add a certain amount of solvent toluene and octadecyltrimethoxysilane (OTS) into a three-necked flask, mechanically stir at room temperature for 48 hours, and after the reaction is completed, dry the sample at room temperature for 12 hours to obtain the target product, and bag it for later use.
[0111] Figure 3 The macroscopic morphology of the prepared polymer gel particles is shown in Figure 1. As can be seen from the figure, these particles are spherical and have a size distribution between 2-3 mm, showing relatively consistent size characteristics. In addition, the particle surface is smooth and regular in shape, without obvious bumps or defects.
[0112] Figure 4 The cross-sectional scanning electron microscope image of the prepared polymer gel particles. As can be seen from the figure, although the polymer gel particles are relatively rough inside, their structure presents a relatively dense striped layered structure. This internal morphology gives the gel particles a certain water absorption capacity and compressive strength and improves their stability, thereby better controlling the morphology of the polymer gel particles. The ionic liquid crosslinker changes the internal structure of the polymer gel particles and improves their mechanical properties.
[0113] Figure 5 The FTIR spectrum of P(AA-AM-ILs) was analyzed at 3436cm -1 The characteristic absorption peak of (-NH2) is at 2900cm -1 The stretching vibration peak of the imidazole ring (=CH) appears nearby with obvious intensity, 1165cm -1 The stretching vibration peak of (NC) is 1557cm -1 The stretching vibration peak of the imidazole ring (C=N) at 723 cm -1 It is the vibration absorption peak of long-chain alkyl, indicating that there are long alkyl chains contained in the ionic liquid in the polymer gel particles.
[0114] Figure 6This is the thermal stability analysis of the synthesized polymer gel at 30℃-800℃, and the test results under N2 atmosphere. As can be seen from the figure, the weight of the sample continues to decrease with the increase of temperature. The mass loss changes of the two gels are basically the same, and there are three weight loss stages. The first stage is around 210℃, and these weight losses can be attributed to the evaporation of adsorbed water in the gel particles. The thermal degradation of the two polymer gels in the second stage is between 210℃-350℃, which is mainly caused by the thermal decomposition of various oxygen-containing functional groups. The third stage is the final decomposition stage of the sample at high temperature, and the copolymer gel is between 350℃-473.2℃, which is mainly caused by the decomposition of the CC bonds on the side chains and main chains of the polymer gel under heat and more severe structural destruction. The results show that ionic liquids as crosslinkers can improve the thermal stability of polymer gel particles and increase their usability under high temperature conditions.
[0115] Embodiment 1:
[0116] Preparation of prepolymer solution
[0117] Add 1.6199g acrylic acid, 6mL distilled water and 0.7193g sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 2.4299g acrylamide solid and 0.0015g methacrylate-β-hydroxyethyl ester. During the stirring process, add 0.1035g of ionic liquid crosslinker to the above-configured solution. Finally, add 0.0324g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to perform a crosslinking reaction and obtain a prepolymer solution.
[0118] Add 1.6205g acrylic acid, 6mL distilled water and 0.7103g sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 1.7432g acrylamide solid and 0.0013g β-hydroxyethyl methacrylate. During the stirring process, add 0.1553g of ionic liquid crosslinker to the above-configured solution. Finally, add 0.0247g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to perform a crosslinking reaction and obtain a prepolymer solution.
[0119] Add 1.6199g acrylic acid, 6mL distilled water and 0.7193g sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 2.4299g acrylamide solid and 0.0015g β-hydroxyethyl methacrylate. During the stirring process, add 0.207g of ionic liquid crosslinker to the above-configured solution. Finally, add 0.0324g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to perform a crosslinking reaction and obtain a prepolymer solution.
[0120] Add 1.6196g of acrylic acid, 6mL of distilled water and 0.7192g of sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 2.4294g of acrylamide solid and 0.0015g of β-hydroxyethyl methacrylate. During the stirring process, add 0.2587g of ionic liquid crosslinker to the above-configured solution. Finally, add 0.0324g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to perform a crosslinking reaction and obtain a prepolymer solution.
[0121] Add 1.6199g acrylic acid, 6mL distilled water and 0.7193g sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 2.4299g acrylamide solid and 0.0015g methacrylate-β-hydroxyethyl ester. During the stirring process, add 0.3105g of ionic liquid crosslinker to the above-configured solution. Finally, add 0.0324g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to perform a crosslinking reaction and obtain a prepolymer solution.
[0122] Add 1.6202g of acrylic acid, 6mL of distilled water and 0.7194g of sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 2.4309g of acrylamide solid and 0.0017g of β-hydroxyethyl methacrylate. During the stirring process, add 0.3623g of ionic liquid crosslinker to the above-configured solution. Finally, add 0.0324g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to perform a crosslinking reaction and obtain a prepolymer solution.
[0123] Add 1.6199g of acrylic acid, 6mL of distilled water and 0.7193g of sodium hydroxide to a 50mL beaker to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, add 2.4299g of acrylamide solid and 0.0015g of β-hydroxyethyl methacrylate. During the stirring process, add 0.414g of ionic liquid crosslinker to the above-prepared solution. Finally, add 0.0324g of initiator potassium persulfate. After all the reagents required for the experiment are added, continue stirring until the mixture is evenly mixed to carry out the crosslinking reaction and obtain a prepolymer solution.
[0124] Embodiment 2:
[0125] Preparation of P(AA-AM-ILs) gel particle plugging agent
[0126] Use a syringe to absorb the prepared prepolymer liquid and drop it into 80℃ constant temperature silicone oil. React for 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with 20ml of tetrahydrofuran. Wash it 3 times and ventilate and dry it at room temperature for 3 hours. Put it in a 70℃ oven and dry it to constant weight to obtain spherical polyacrylamide gel particles. Bag them for later use.
[0127] 1. Specific application fields or related products of the present invention.
[0128] 1. Oilfield exploitation:
[0129] Water plugging agent: used in the water injection development process of oil fields to increase crude oil recovery by plugging high permeability layers or water channeling channels.
[0130] Profile control agent: used in oil wells to improve the water injection profile and enhance the water injection effect.
[0131] 2. Natural Gas Extraction:
[0132] Natural gas hydrate mining: In the process of natural gas hydrate mining, it is used to control the penetration and flow of water and improve mining efficiency.
[0133] 2. Relevant evidence of the technical effects obtained by the embodiments of the present invention.
[0134] Depend on Figure 7It can be seen that different concentrations of ionic liquid crosslinkers have a significant effect on the compressive strength of polymer gel particles. In the early stage, as the content of the crosslinker increases, the compressive strength gradually increases, which is because more crosslinkers strengthen the structural stability of the gel particles. As the content of the crosslinker increases further, the compressive strength begins to decrease, which is because the excessive crosslinker leads to excessive crosslinking of the internal structure of the gel particles. The experimental results show that when the content of the ionic liquid crosslinker reaches 1.5%, the compressive strength of the polymer gel particles reaches the maximum value. This shows that within a certain range, an appropriate amount of ionic liquid crosslinker can effectively enhance the mechanical properties of the gel particles. It can be seen from the figure that with the increase of temperature, the compressive strength of the gel particle plugging agent gradually increases. The addition of the ionic liquid crosslinker significantly improves the strength of the gel particles, and the ionic liquid itself has high mechanical properties, which increases its compressive strength. When the content of the ionic liquid crosslinker is 1.5%, the strength of the gel particle plugging agent gradually decreases because the crosslinking strength is too large as the content increases, resulting in a smaller expansion change of the gel particles after absorbing water, and the compressive strength will also gradually decrease.
[0135] from Figure 6 It can be seen that the weight of the sample decreases continuously with the increase of temperature. The mass loss changes of the two gels are basically the same, and there are three weight loss stages. The first stage is around 210℃, and these weight losses can be attributed to the evaporation of adsorbed water in the gel particles. The thermal degradation of the two polymer gels in the second stage is between 210℃-350℃, which is mainly caused by the thermal decomposition of various oxygen-containing functional groups. The third stage is the final decomposition stage of the sample at high temperature, the copolymer gel ILs (A) is between 350℃-473.2℃, and the copolymer gel is between 350℃-470.1℃, which is mainly caused by the decomposition of the CC bonds on the side chains and main chains of the polymer gel under heat and more severe structural destruction. The results show that ionic liquids as crosslinkers can improve the thermal stability of polymer gel particles and increase their performance under high temperature conditions.
[0136] Figure 8The figure is a curve showing the relationship between the water absorption rate of polymer gel particles coated with octadecyltrimethoxysilane and temperature. As can be seen from the figure, the effect of octadecyltrimethoxysilane is very obvious. The water absorption rate of the polymer gel particles after coating is very low under low temperature conditions. As the temperature rises, the octadecyltrimethoxysilane gradually dissolves and falls off, and the polymer gel particles begin to absorb water when exposed to water, achieving the purpose of hydrophobicity at low temperatures and water absorption under high temperature conditions. The reason why octadecyltrimethoxysilane can be used as a surface coating material: there are non-polar Si-OH bonds in the molecular structure, and surface tension will be generated between molecules on the liquid surface. Since the surface tension between water molecules is generally large, it is easy to adsorb together. Hydrophobic substances generally have very small surface tension, which causes uneven distribution of water molecules on their surfaces, forming a hydrophobic effect. The surface tension of octadecyltrimethoxysilane is smaller than that of water molecules, so it has a higher hydrophobicity.
[0137] Fig. 9 The contact angle of the polymer gel particles coated with octadecyltrimethoxysilane is used to measure the wettability of the solid surface. When the contact angle is >90°, the solid surface is hydrophobic; when the contact angle is <90°, the solid surface is hydrophilic. The contact angle of the polymer gel particles in the figure is 130.2°, and the solid surface is typically hydrophobic, indicating that octadecyltrimethoxysilane is successfully coated on the surface of the polymer gel particles.
[0138] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent, It is characterized in that The structure of the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent is as follows:
2. The functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent as claimed in claim 1, It is characterized in that The functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent adopts a copolymer of acrylic acid AA and acrylamide AM as a basic gel material.
3. A method for preparing a functional ionic liquid enhanced polyacrylamide based gel particle plugging agent according to any one of claims 1 to 2, It is characterized in that The method for preparing the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent comprises: (1) Preparation of prepolymer solution; (2) Preparation of P(AA-AM-ILs) gel particle plugging agent; (3) Coated gel particle plugging agent.
4. The method for preparing the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent as claimed in claim 3, It is characterized in that Preparation of the prepolymer solution; Add acrylic acid and 6 mL of distilled water to a 50 mL beaker. Slowly add sodium hydroxide under magnetic stirring and ice-water bath conditions to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, weigh a certain amount of acrylamide solid and add it; Then weigh a certain amount of β-hydroxyethyl methacrylate and slowly add it; during the stirring process, add a certain amount of ionic liquid crosslinking agent to the above-prepared solution, and the addition amount is as shown in the table; finally, add potassium persulfate with a total weight of 0.8% of acrylic acid and acrylamide, and ensure that no solid remains on the wall of the cup during the addition process; after all the reagents required for the experiment are added, continue to stir until the mixture is evenly mixed to perform a crosslinking reaction to obtain a prepolymer solution.
5. The method for preparing the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent according to claim 4, It is characterized in that The mass ratio of acrylamide to acrylic acid is 6:
4.
6. The method for preparing the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent as claimed in claim 3, It is characterized in that Preparation of the P(AA-AM-ILs) gel particle plugging agent: Use a syringe to absorb the prepared prepolymer liquid and drop it into 80℃ constant temperature silicone oil. Be careful not to have bubbles when the syringe absorbs the precursor liquid. React for 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with tetrahydrofuran. Wash it several times, ventilate and dry it at room temperature for 3 hours, put it in a 70℃ oven, and dry it to constant weight to obtain spherical polyacrylamide gel particles, which are bagged for later use.
7. The method for preparing the functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent as claimed in claim 3, It is characterized in that The coated gel particle plugging agent: The spherical gel particle plugging agent was coated with octadecyltrimethoxysilane. The specific operation steps were as follows: a certain amount of solvent toluene and octadecyltrimethoxysilane (OTS) were added to a three-necked flask, and mechanical stirring was performed at room temperature for 48 hours. After the reaction was completed, the sample was dried at room temperature for 12 hours to obtain the target product, which was then bagged for later use.
8. A system for preparing a functional ionic liquid enhanced polyacrylamide based gel particle plugging agent according to any one of claims 3 to 7, It is characterized in that The functional ionic liquid enhanced polyacrylamide-based gel particle plugging agent preparation system comprises: The prepolymer liquid preparation module is used to add acrylic acid and 6 mL of distilled water into a 50 mL beaker, and slowly add sodium hydroxide under magnetic stirring and ice water bath conditions to prepare a solution with a neutralization degree of 80%. When the sodium hydroxide is completely dissolved and the solution is colorless and transparent, a certain amount of acrylamide solid is weighed and added; then a certain amount of β-hydroxyethyl methacrylate is weighed and slowly added; during the stirring process, a certain amount of ionic liquid crosslinking agent is added to the above-prepared solution, and the addition amount is as shown in the table, and finally potassium persulfate is added at 0.8% of the total mass of acrylic acid and acrylamide, and the addition process ensures that no solid remains on the wall of the cup; after all the reagents required for the experiment are added, stirring is continued until the mixture is evenly mixed to perform a crosslinking reaction to obtain a prepolymer liquid; The gel particle plugging agent preparation module is used to draw the prepared prepolymer liquid with a syringe and drop it into the 80°C constant temperature silicone oil. When the syringe draws the precursor liquid, be careful not to have bubbles. The reaction is 5-8 minutes. After the reaction is completed, remove it from the silicone oil and clean the silicone oil on the surface with tetrahydrofuran for several times. Dry it for 3 hours under ventilation at room temperature, put it in a 70°C oven, dry it to constant weight, and obtain spherical polyacrylamide gel particles, which are bagged for later use; The coated gel particle plugging agent module is used to coat the spherical gel particle plugging agent with octadecyltrimethoxysilane. The specific operation steps are as follows: add a certain amount of solvent toluene and octadecyltrimethoxysilane (OTS) into a three-necked flask, mechanically stir at room temperature for 48 hours, and after the reaction is completed, dry the sample at room temperature for 12 hours to obtain the target product, and bag it for later use.
Citation Information
Cited By
Preparation method of temperature-resistant and salt-resistant nano-micro jelly
CN120888092A
